Isolation, Screening, and Optimization of Amylase-Producing Endophytic Bacteria from Rhizophora apiculata - Agustina Monalisa Tangapo; Susan Marlein Mambu; Pience Veralyn Maabuat; Dwina Kristianti; Williando Ering; Lalu Wahyudi (Universitas Sam Ratulangi, 2025)
High amylase enzyme production requires optimal supporting factors for enzyme production. The purpose of this study was to determine the optimum conditions for endophytic bacterial fermentation, including substrate concentration, pH, and fermentation temperature, for the production of amylase from endophytic bacteria of mangrove plants Rhizophora apiculata. Analysis of amylase enzyme activity was carried out using the 3,5-dinitrosalicylic acid (DNS) assay. The results obtained from this research were from a total of 18 endophytic bacteria R. apiculata that were successfully isolated, 6 bacterial isolates were obtained which showed the ability to produce extracellular amylase. The potential of bacteria for amylase production grown on 0.5% starch media was determined based on the ratio between the diameter of the halo zone and the diameter of the bacterial colony. Three isolates were selected, EB.5, EB.10, and EB.12 for further optimization of the fermentation conditions for amylase production. Based on the results obtained, it was shown that the fermentation conditions for amylase enzyme from the three isolates of endophytic bacteria were optimum in media with a concentration of 1.5% starch, in media with a pH of 6, and optimum in the temperature range of 30oC.